Thoughts on phronesis. Issue 2 (3rd April 2019) - Burbules, Nicholas C.
ABSTRACT: This essay explores the concept of phronesis in two contexts: phronesis as a virtue, in fact a meta-virtue because it guides the exercise of other virtues; and phronesis as an element in theories of practice. I argue that these two aspects are closely related, because ethics – especially virtue ethics – is best understood as a kind of practice. The second part of the essay explores some of the consequences of thinking about ethics in this way.